Learning strategies applied by the students in writing English text - Dwiana Binti Yulianti (Journal on English as a Foreign Language, 2018)
This study is aimed at verifying the finding of a study on what learning strategies applied by the students in writing text and the impact of learning strategies toward the students’ writing score. This is a qualitative descriptive study, and it is conducted at Communication Science Department of the Muhammadiyah University of Ponorogo. The instruments used to collect the data were observation, documentations, and questionnaire. After analyzing the data, it is found that the learning strategies used by the students in writing English text are metacognitive strategies, compensation strategies, cognitive strategies, affective strategies, memory strategies, and social strategies. The students use learning strategies in moderate level which means they sometimes use these learning strategies. Moreover, learning strategies influence the students’ writing score; the students who get good score use metacognitive strategies and the students who get fair score use affective strategies.